2015
DOI: 10.1177/0363546515594446
|View full text |Cite
|
Sign up to set email alerts
|

Knee Kinematics During Noncontact Anterior Cruciate Ligament Injury as Determined From Bone Bruise Location

Abstract: Background The motions causing non-contact ACL injury remain unclear. Tibiofemoral bone bruises are believed to be the result of joint impact near the time of ACL rupture. The locations and frequencies of these bone bruises have been reported, but there is limited data quantifying knee position and orientation near the time of injury based on these contusions. Hypothesis Knee position and orientation near the time of non-contact ACL injury include extension and anterior tibial translation. Study Design Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(132 citation statements)
references
References 66 publications
10
112
3
Order By: Relevance
“…15,22 Moreover, 2 recent studies demonstrated that a large anterior tibial translation was measured in patients at the predicted position of injury. 16,24 Given that the ACL is a primary restraint to anterior shear loading, a large anterior tibial translation could produce large anterior tibial shear forces and cause an ACL injury. 38 Therefore, these results combined together suggest that anterior tibial shear force in the sagittal plane could also be a key risk factor for ACL injuries.…”
Section: Bone Bruise Patternsmentioning
confidence: 99%
“…15,22 Moreover, 2 recent studies demonstrated that a large anterior tibial translation was measured in patients at the predicted position of injury. 16,24 Given that the ACL is a primary restraint to anterior shear loading, a large anterior tibial translation could produce large anterior tibial shear forces and cause an ACL injury. 38 Therefore, these results combined together suggest that anterior tibial shear force in the sagittal plane could also be a key risk factor for ACL injuries.…”
Section: Bone Bruise Patternsmentioning
confidence: 99%
“…Using the same technique, Brown et al 39 found that landing with an increased initial knee flexion angle decreased peak ACL length during both prelanding and landing phases of a drop vertical jump task. Kim et al 40 recently estimated knee kinematics at the time of ACL injury for eight patients following ACL injuries through reconstruction of the relative positions of the femur and tibia at the time of ACL injury by maximizing the contact of bone bruise areas between the femur and tibia in MRI. Their results showed a mean tibial anterior translation of 22 mm, a mean knee flexion angle of 12 , and a mean knee valgus angle of 5 at the time of ACL injury.…”
Section: Loading Mechanismsmentioning
confidence: 99%
“…They concluded that knee valgus motion along with an almost extended knee are risk factors that cause ACL strain. In a similar study, Kim et al (29) found that the mean angle of knee valgus was 5° at the time of ACL tear in eight patients. The present study evidenced statistically significant differences between the two groups in the case of KFA observed during both the jump with the least ground contact time and the three trials' mean KFA, with the mean KVAs ranging from 4.10° to 5.50°.…”
Section: Discussionmentioning
confidence: 76%